2012
DOI: 10.1186/1471-2458-12-567
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of cancer in patients with type 2 diabetes mellitus: A retrospective cohort study in China

Abstract: BackgroundPrevious studies indicated that type 2 diabetes mellitus (T2DM) might be associated with the risk of cancer. The aim of this study was to investigate the association between T2DM and the risk of developing common cancers in a Chinese population.MethodsA population-based retrospective cohort study was carried out in the Nan-Hu district of Jiaxing city, Zhejiang province, China. The incidence of cancer cases among type 2 diabetic patients were identified through record-linkage of the Diabetic Surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 43 publications
(54 reference statements)
6
57
0
Order By: Relevance
“…Several epidemiological studies have observed an increased risk of cancer (22)(23)(24)(25)(26), including stomach cancer (27)(28)(29), colon, breast, endometrial, liver, pancreatic and bladder cancer (30,31), and prostate cancer (32), in DM patients; however, the precise underlying mechanisms have not been elucidated. Factors such as insulin resistance, secondary Table II.…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies have observed an increased risk of cancer (22)(23)(24)(25)(26), including stomach cancer (27)(28)(29), colon, breast, endometrial, liver, pancreatic and bladder cancer (30,31), and prostate cancer (32), in DM patients; however, the precise underlying mechanisms have not been elucidated. Factors such as insulin resistance, secondary Table II.…”
Section: Discussionmentioning
confidence: 99%
“…However there were still some limitations in this published meta-analysis: (1) The studies and samples were insufficient for which did not contained many new studies with a large number of samples which reported in recent years (Manami et al, 2006;Rousseau, 2006;Susanna et al, 2008;Li et al, 2011;MacKenzie et al, 2011;Tseng, 2011;Attner et al, 2012;Zhang et al, 2012;Newton et al, 2013;Prizment et al, 2013). So the population included in it was too small to reveal the actual relationship between DM and the bladder cancer risk.…”
Section: Diabetes Mellitus Increases the Risk Of Bladder Cancer: An Umentioning
confidence: 99%
“…To date, many large sample epidemiological studies have investigated the important role of DM in bladder cancer development. The results were inconsistent or even contradictory, some of studies did not support an association of DM with overall bladder cancer incidence (Rousseau et al, 2006;Larssona et al, 2008;Zhang et al, 2012). So after removing the three unqualified literature (Kessler, 1970;Kantor et al, 1984;Verlato et al, 2003), adding the new studies which were not included in above meta-analysis, we performed a meta-analysis of 23 published studies covering 643,683 cases and 4,819,656 controls to get a more precise evaluation of the association between DM and the risk of bladder cancer.…”
Section: Diabetes Mellitus Increases the Risk Of Bladder Cancer: An Umentioning
confidence: 99%
See 2 more Smart Citations